Public Service Quality During The COVID-19 Pandemic In Banten Province (Case Study: E-Sambat Application) - Moh. Ali Hanapiah; Heru Nurasa; Ida Widianingsih; Ramadhan Pancasilawan (Aliansi, 2022)
Public services are a series of activities carried out by the public bureaucracy to meet the needs of service users. Therefore, the quality of public services must be in accordance with customer expectations and this means that government organizations must always be responsive and anticipatory to any changes in customer needs. Motor Vehicle Tax is the largest source of regional tax revenue in Banten Province, various efforts have been made by the local government both extensification and intensification in increasing regional income, one of which is through motor vehicle tax levies as a form of digital public service carried out in Samsat around the world. Banten Province. The purpose of this study is to find out the performance of Public Services in Banten Province, especially regarding the application of e-Sambat during the Covid-19 Pandemic, what are the obstacles and efforts in public services related and carried out by the Banten Provincial Government. This research uses a descriptive qualitative approach. In collecting the data, this research uses observation, interviews, book studies, and internet searching. Data collection in this research was carried out with existing literature review.